Baricitinib represses the myocardial fibrosis via blocking JAK/STAT and TGF-β1 pathways in vivo and in vitro - Renlei Feng; Hongli Liu; Yunqing Chen (BMC Cardiovascular Disorders)
Abstract Background JAK/STAT pathway is closely involved in the organ fibrotic process. The current study aimed to investigate the impact of baricitinib, an oral selective JAK1/JAK2 inhibitor, on the myocardial fibrosis in vivo and the activation of cardiac fibroblasts in vitro. Methods The mouse myocardial fibrosis model was established by isoproterenol (ISO) treatment, then was treated by baricitinib. The activation of mouse cardiac fibroblasts was established by TGF-β1 stimulation, then was treated by baricitinib with several concentrations. Besides, JAK2 was knocked down by small interfering RNA (siRNA) in TGF-β1-stimulated mouse cardiac fibroblasts. Results Baricitinib not only attenuated myocardial cell widening, inflammatory infiltration, fibrous tissue, and heart index, but also reduced collagen volume fraction, the expressions of Col1, Col3, α-SMA, Fn, MMP9, and TIMP1 in ISO-induced myocardial fibrosis mice. Meanwhile, baricitinib decreased the expressions of p-STAT3 and TGF-βRII in these mice. Interestingly, in TGF-β1-stimulated cardiac fibroblasts, baricitinib decreased the expressions of Col1, Col3, α-SMA, Fn, MMP9, and TIMP1 in a dose-dependent manner (From 10 to 2000 nM), also exhibited a dose-dependent impact on the expressions of p-STAT3 and TGF-βRII. Finally, JAK2 knockdown by siRNA downregulated the expressions of Col1, Col3, α-SMA, and Fn in TGF-β1-stimulated cardiac fibroblasts. Conclusion Inhibition of JAK/STAT pathway by baricitinib represses the myocardial fibrosis in vivo and in vitro, indicating baricitinib may be a treatment option for myocardial fibrosis, while further validation is needed.